Cerebral glucose changes after chemotherapy and their relation to long-term cognitive complaints and fatigue - Schroyen, Gwen; Schramm, Georg; Van Weehaeghe, Donatienne; Leenaerts, Nicolas; Vande Casteele, Thomas; Blommaert, Jeroen; Koole, Michel; Smeets, Ann; Van Laere, Koen; Sunaert, Stefan; Deprez, Sabine (Frontiers in Oncology, 2022)
Purpose: To investigate the acute cerebral metabolic effects of intravenous chemotherapy and their association with long-term fatigue/cognitive complaints. Experimental design: Using [18F]-FDG-PET/CT whole-body scans, we retrospectively quantified relative cerebral glucose metabolism before and after neoadjuvant chemotherapy in a cohort of patients treated for non-metastatic breast cancer(2009-2019). Self-report of cognitive complaints and fatigue were prospectively assessed 7±3 years after therapy. Metabolic changes were estimated with i) robust mixed-effects modelling in regions-of-interest (frontal, parietal, temporal, occipital, and insular cortex) and ii) general-linear modelling of whole-brain voxel-wise outcomes. iii) The association between metabolic changes and self-reported outcomes was evaluated using linear regression-analysis. Results: Of the 667 screened patients, 263 underwent PET/CT before and after chemotherapy and 183(48±9 years) met the inclusion criteria. After chemotherapy, decreased frontal and increased parietal and insular metabolism were observed (|ß|>0.273, pFDR<0.008). Separately, additional increased occipital metabolism after epiribucin+ cyclophosphamide (EC) and temporal metabolism after EC+ fluorouracil chemotherapy were observed(ß>0.244, pFDR0.048). Voxel-based analysis(pcluster-FWE<0.001) showed decreased metabolism in the paracingulate gyrus(-3.2±3.9%) and putamen(3.1±4.1%) and increased metabolism in the lateral cortex(L=2.9±3.1%) and pericentral gyri(3.0±4.4%). Except for the central sulcus, the same regions showed changes in EC, but not in FEC patients. Of the 97 self-reported responders, 23% and 27% experienced extreme fatigue and long-term cognitive complaints, respectively, which were not associated with metabolic changes. Conclusion: Combined with earlier findings, this study supports inflammatory mechanisms resulting in relative hypermetabolism, mainly in the parietal/occipital cortices. As early metabolic changes did not precede long-term complaints, further research is necessary to identify vulnerable patients.